Gender Test Score Gaps Under Equal Behavioral Engagement. (August 2020) - Pyne, Jaymes
Girls tend to do better than boys academically, in part because they are more engaged in school. What if they weren't? Using nationally representative data, I examine how equal starting points and trajectories of behavioral engagement in elementary school could change gender test score gaps. I find that equal engagement patterns could entirely reverse girls' average leads over boys in fifth-grade reading test score achievement and could more than triple the average math test score gender gap currently favoring boys. These findings call into question narratives about favoritism towards girls in schools, instead highlighting educational advantages boys may enjoy despite being typically far less engaged in school than girls.